Sistem Pendukung Keputusan Pemilihan Jurusan Di Sekolah Menengah Kejuruan 1 Cengkareng Jakarta - Asri Wahyuni (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2017)
Decision support system is a computerized system designed to improve the effectiveness of decision-making to solve problems that are semi-structured and structured so that in the decision-making process can be more qualified. The decision to choose a course in school should be accurate. Apprenticeship for Vocational High School (SMK) 1 students of Cengkareng Jakarta is conducted at the time of admission of new students. Students will decide what majors are chosen, a common problem is the difficulty in the process of placement of students in choosing majors who are still not sure of the students choose departments that eventually dissolved because the majors are not in accordance with ability. Decision Support System Design is built using PHP and MySQL as well as Adobe Dreamweaver CS6 software. By using the software then the website work will be faster and easier. The tables used in the making of this web are student tables, department tables, consulting tables majors, user tables, opinion tables, academic tables, report card grades, and info tables. All the tables are used to accommodate the data needed in building the website